Tacrolimus and sirolimus in capillary dried blood spots allows for remote monitoring. (21st November 2014) - Dickerson, Jane A.; Sinkey, Marian; Jacot, Kathleen; Stack, Jennifer; Sadilkova, Katerina; Law, Yuk M.; Jack, Rhona M.
Abstract Therapeutic drug monitoring of tacrolimus and sirolimus plays a significant role in the clinical follow‐up of transplant patients receiving IMS therapy. Success of transplant and favorable patient outcome relies on maintaining adequate therapeutic drug levels. The purpose of this research is to assess the clinical utility of remote collection of DBS for immunosuppressant monitoring and compare the IMS level in paired collections of venous whole blood and DBS. Sirolimus and tacrolimus levels were clinically correlated in capillary blood collected from a finger poke with venous whole blood from pediatric, post‐transplant patients. The participants took the dried blood spot card home with them with a pre‐addressed, postage‐paid envelope and mailed it back to the laboratory. Overall, a small but statistically significant negative bias was observed (−0.6 ng/mL, p = 0.0011). A chart review was performed to assess whether clinical management would have changed, and none of the cases revealed a clinically significant change. Sirolimus in DBS also correlated with venous levels. Overall, a small but statistically negative bias was observed (−0.8 ng/mL, p = 0.029). In summary, analysis of IMS levels in DBS is possible, and the difference noted between capillary and venous blood is within the clinically acceptable limits.